POTENSI SENI KRIYA ISTIMEWA DALAM PAMERAN âNEGARI NGAYOGYAKARTA HADININGRAT 2012â - Eskak, Edi (CORAK, 2012)
Arts Festival Negari Ngayogyakarta Hadiningrat 2012 undertaken in order to commemorate the first century of Hamengku Buwono IX as well as 2,5 century of Ngayogyakarta Hadiningrat, featuring the character or the privilege of Yogyakarta through works of art by artists with no exit from the corridors of copyrighted artistic distinctiveness. The works on display most of the particular character, specific and have their own specialty. Privileges of Yogyakarta with its dynamic, multicultural, and tolerant of the works reflected on display in the various mediums of expression and creation. A wide assortment of works of art displayed expression of both the traditional, conventional and non conventional, such as: painting, graphics, sculpture, video, film, animation, installation, performance art, digital prints, puppets, mixed media and others. Not to mention that the exhibition has a variety of craft works of art, such as the art which haselements of craftmanship. The uncommon art that relies on creativity ideas and handskills in this exhibition appear surprisingly with exceptional works that have creative potential prospective. These young artists, among other craft; Karyadi, Fitriasih Pudyo Atmaningrum, I Gde Suryawan, and I Gusti Ngurah Edi Basudewa.Keywords: potential, arts crafts, specialty, and Negari Ngayogyakarta Hadiningrat